Investigasi Ketersediaan Air Permukaan Sungai Kapur Solok Selatan Untuk Kebutuhan Air Baku - Zufrimar Zufrimar; Edwina Zainal (Jurnal Ilmiah Rekayasa Sipil, 2020)
South Solok Regency with a population of more than 163,000 people, 62.3% without access to clean water services through the Domestic Water Company (PDAM). The number of PDAM customers has been changed in Solok Selatan Regency in the last five years. Since the water capacity is very limited which means it difficult to increase the number of customers, so it is predicted to be unable to meet the increasing need for clean water. Based on the study of the potential for raw water availability in the South Solok Regency, Sungai Kapur has the potential as a source of raw water. To complete the potential study, it is necessary to know the quantity of raw water by examining hydrological parameters to optimize the planning of water resources potential. The quantity of raw water is assessed by the dependable flow to determine the low flow characteristic. Based on calculations, obtained a reliable discharge of 90% in monthly that can be used as raw water. The raw water source used has a discharge of ± 138.6 l / sec. However, the availability is uneven throughout the month, so a reservoir is needed to guarantee the availability of raw water for residents. In addition, raw water quality is assessed in terms of physical, chemical, and biological aspects. The results of the raw water quality test in the Sungai Kapur are eligible for raw water based on Government Regulations No. 82, 2001